Psychological Characteristics Affecting the Adoption of Agricultural Technologies (Indian Journal of Extension Education, 2015)
A study was conducted to find out the influence of psychological characteristics in adoption of low cost technologies by farmwomen having small and marginal land holding. The study was conducted under Madhya Pradesh Women in Agriculture Programme in Katni district of Madhya Pradesh. Data were collected through pretested structured interview schedule and the relationship between the dependent variables and adoption was studied using correlation analysis. The study leads to the conclusion that both the categories of beneficiaries had different level of adoption. The psychological attributes of the beneficiaries like economic motivation, risk orientation, scientific orientation and knowledge were found to be positively and significantly correlated with the adoption of low cost technologies taken under MAPWAprogramme.